EFEKTIVITAS MODEL KOOPERATIF TIPE STUDENT ACTIVE LEARNING BERBANTUAN MEDIA PAPAN PINTAR DALAM MENINGKATKAN PEMAHAMAN KONSEP IPAS SISWA KELAS IV UPT SD - Irma Kristiani Br Ginting; Frida Marta Agareta Simorangkir; Heka Maya Sari Br Sembiring; Regina Sipayung; Darinda Sofia Tanjung (Universitas Negeri Medan, 2025)
This study was conducted in class IV of SD Negeri 060933 Medan Johor and aimed to describe the effectiveness of the Studen Active Learning cooperative model assisted by smart boards in improving students' understanding of IPAS concepts. The research method used a quantitative approach and the sample size was 25 students. The researcher first conducted a pretest with an average score of 50.6, which was classified as poor. After the researcher used the Studen Active Learning cooperative model, the posttest results showed an improvement with an average score of 84.2, which was classified as good. The results of the questionnaire for fourth-grade students had an average score of 81.88, with the highest score obtained by a student being 92 and the lowest score obtained by a student being 68. This shows that the learning outcomes using the Cooperative Student Active Learning model assisted by smart board media in improving the conceptual understanding of fourth-grade students were in the excellent category. The results of this study show that the t-test results also show a t-count value greater than t-table (11.897≥2.064), which means that there is a significant effect of using the Cooperative Student Active Learning model assisted by smart board media in improving the understanding of science concepts among fourth-grade students at UPT SD Negeri 060933 in the 2024/2025 academic year.